UPAYA PENINGKATAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI KEGITAN MENJAHIT PADA ANAK KELOMPOK B TK IT AL-MUNAWWARAH LONG KALI TAHUN PELAJARAN 2021/2022 - Soleha, Wahyuni; Sjamsir, Hasbi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
The purpose of this study was to improve children's fine motor skills through sewing activities using classroom action research methods which were carried out in two cycles, each cycle covering the stages of planning, implementing, observing and reflecting. The results show that the percentage of pre-cycle completeness, namely 30% (3 children) of children completed and then given action, increased in cycle I to 50% (5 children) and cycle II to 90%, namely 9 children have completed. So that sewing activities can improve the fine motor skills of group B children at TK IT Al-Munawwarah Long Kali for the 2021/2022 academic year.